Oestrone‐targeted liposomes for mitoxantrone delivery via oestrogen receptor – synthesis, physicochemical characterization and in‐vitro evaluation. (26th April 2017) - Hao, Qiang; Xu, Guoxing; Yang, Yue; Sun, Yuxin; Cong, Dengli; Li, Hongrui; Liu, Xin; Wang, Zeng; Zhang, Zheng; Chen, Jinglin; Li, Yao; Luan, Xue; et al.
Abstract: Objectives: Targeted delivery of mitoxantrone (MTO, an anthraquinone drug with high antitumour effect) may be achieved using a novel nanoparticulate delivery system via binding the oestrogen receptor (ER, highly expressed in a variety of human tumours). Methods: A novel liposomal nanoparticle (NP) was developed using a conjugate derived from 1, 2‐distearoyl‐sn‐glycero‐3‐phosphoethanolamine‐N‐[amino (polyethylene glycol)‐2000] (DSPE‐PEG2000 ‐NH2 ) and oestrone (ES, is known to bind the ER) to produce an ES‐targeted PEGylated liposome (ES‐SSL). The resulting targeted NP was loaded with MTO to produce a targeted liposome‐MTO formulation (ES‐SSL‐MTO). Key findings: The targeted formulation (~140 nm, 1.5 mV) achieved over 95% drug encapsulation efficiency and a favourable stability at 4, 25 and 37 °C up to 48 h. The flow cytometric data indicated that cellular uptake of ES‐SSL into human leukaemia HL‐60 cells was mediated via binding the oestrogen receptor. In addition, the ES‐SSL‐MTO significantly reduced the growth of HL‐60 cells. Conclusions: Our results provide a proof of principle that ES‐modified PEGylated liposomes can target the ER, thereby potentially improving the therapeutic benefits in ER‐overexpressed tumours.